2022
DOI: 10.1093/eurjpc/zwac029
|View full text |Cite
|
Sign up to set email alerts
|

How spaceflight challenges human cardiovascular health

Abstract: The harsh environmental conditions in space, particularly weightlessness and radiation exposure, can negatively affect cardiovascular function and structure. In the future, preventive cardiology will be crucial in enabling safe space travel. Indeed, future space missions destined to the Moon and from there to Mars will create new challenges to cardiovascular health while limiting medical management. Moreover, commercial spaceflight evolves rapidly such that older persons with cardiovascular risk factors will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…In addition to cardiovascular function, the ax parameter could be also useful for the assessment of cerebral drainage. Indeed, in challenging condition such as spaceflight, showed a microG time-exposure relation, decreasing during flight permanence, followed by a normalization at return to the Earth [ 8 , 9 , 10 ]. Therefore, the use of this parameter becomes useful for monitoring the influence of exercise on cerebral venous drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cardiovascular function, the ax parameter could be also useful for the assessment of cerebral drainage. Indeed, in challenging condition such as spaceflight, showed a microG time-exposure relation, decreasing during flight permanence, followed by a normalization at return to the Earth [ 8 , 9 , 10 ]. Therefore, the use of this parameter becomes useful for monitoring the influence of exercise on cerebral venous drainage.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the reduction of cardiac output in cosmonauts during long term exposure to micro-G is associated with cognitive alterations and visual disturbances. Microgravity exposure causes the shift of fluid to the upper part of the body, inducing an increase of intracellular and interstitial fluid volume [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Health is key for any successful mission, and space agencies are searching for reliable, durable, versatile, and non-complex health monitoring and diagnostic solutions. In manned space flight the cardiovascular system is especially at risk [1]. To offer a possible solution for the future, the authors developed a wearable sensor system that may provide low weight and low maintenance cardio-vascular monitoring which is nevertheless comfortable and continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding cardiovascular risk factors and preventive cardiology will be a key component of safe long-term space travel. 49 , 50 Targeted preventive measures, or countermeasures in aerospace medicine, and identifying vascular risks early will be essential in maintaining cardiovascular performance and health during future space missions. The cardiovascular system undergoes major changes in cardiac parameters, from orthostatic intolerance, arrhythmias, and aerobic capacity to cardiac atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to diminishing physical activity, this can lead to poorer orthostatic tolerance after return to Earth. 50 The space environment may directly impact vascular health; however, the clinical relevance of these findings in terms of morbidity and mortality is unclear at this point in time. Van loon and colleagues developed an open-source lumped mathematical model of the cardiopulmonary system that can simulate the short-term adaptations of crucial hemodynamic parameters to an active stand test after being exposed to microgravity.…”
Section: Introductionmentioning
confidence: 99%